The Linkage of Social Networks and Norms with the Sustainability of the Practice of “Marosok” - Qamara, Cori; Alianta, Aditya Alqamal; Hamdi, Hamdi; Widiarta, I.P.G Didik; Aprylasari, Dede (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
In West Sumatra, "Marosok" is one of the traditional payment methods that is still in use. Finger signals are used to determine the price in this traditional way of buying and selling animals. The transaction takes place beneath a sheet of cloth. In light of this, the purpose of this study is to ascertain how social networks and norms relate to the sustainability of "Marosok" in West Sumatra's livestock purchasing and selling. Purposively selected, 30 respondents (10 farmers, 10 animal traders, and 10 intermediary traders) participated in this study. In order to compile the debate, the research methodology employed is Mixed Method Research, which blends quantitative and qualitative data. Data triangulation was used to examine qualitative data, and choreography was used to study quantitative data. The findings indicate a high linkage between the sustainability of "marosok" and social networks and norms. The findings of key informant interviews provide support for the data. Therefore, "marosok" is still being used in West Sumatra today. Cohesion between buyers, sellers, and middlemen in the purchase and sale of livestock is naturally formed by the application of "marosok," which preserves the value of customs. In the application of "marosok," communal norms are also strictly adhered to. This study can serve as a guide for the community to comprehend how trust-based business transactions between buyers and sellers could support general economic growth